Solusi Limbah Plastik Tak Terpakai Dengan Pirolisis Modular Untuk Bank Sampah Go Green Desa Banyuanyar, Kabupaten Sampang - Millah, Ibrahim saiful; Fardany, A Labib; Mahmudah, Norma; Afandi, Achmad; Apriningwulan, Pusparini (Faculty of Engineering University of Pahlawan Tuanku Tambusai, 2023)
Plastic has the characteristic of being difficult to decompose. Plastic takes 50 - 200 years to decompose in soil (M, Sugito, & Atmaja, 2018). Waste management in Banyuanyar village, Sampang Regency was initiated by a community movement called Go Green to establish a waste bank. This waste bank recycles organic waste into fertilizer and makes vases from plastic, bags from plastic, chairs from fabric and plastic waste, mats from plastic, and other ornaments which are done on Sundays. Valuable plastics like beverage bottles can be resold for assets. Meanwhile, hard-to-process plastics are usually disposed of in landfills. With the presence of pyrolysis, all waste can be processed by the Go Green community. 2 kg of plastic can produce 380 ml of liquid fuel through pyrolysis.